Environmental Toxicants-Induced Immune Responses in the Olfactory Mucosa - Imamura, Fumiaki; Hasegawa-Ishii, Sanae (Frontiers in Immunology, 2016)
Olfactory sensory neurons (OSNs) are the receptor cells for the sense of smell. Although cell bodies are located in the olfactory mucosa of the nasal cavity, OSN axons directly project to the olfactory bulb that is a component of the central nervous system (CNS). Because of this direct and short connection from this peripheral tissue to the CNS, the olfactory system has attracted attention as a port-of-entry for environmental toxicants that may cause neurological dysfunction. Selected viruses can enter the olfactory bulb via the olfactory mucosa, and directly affect the CNS. On the other hand, environmental toxicants may induce inflammatory responses in the olfactory mucosa, including infiltration of immune cells and production of inflammatory cytokines. In addition, these inflammatory responses cause the loss of OSNs that are then replaced with newly generated OSNs that re-connect to the olfactory bulb after inflammation has subsided. It is now known that immune cells and cytokines in the olfactory mucosa play important roles in both degeneration and regeneration of OSNs. Thus, the olfactory system is a unique neuroimmune interface where interaction between nervous and immune systems in the periphery significantly affects the structure, neuronal circuitry, and immunological status of the CNS. The mechanisms by which immune cells regulate OSN loss and the generation of new OSNs are, however, largely unknown. To help develop a better understanding of the mechanisms involved, we have provided a review of key research that has investigated how the immune response in the olfactory mucosa affects the pathophysiology of OSNs.